Aluminosilicate glass with high strength, high modulus and fracture resistance and preparation method and application thereof

By adjusting the raw material components and process flow in aluminosilicate glass, the elastic modulus and fracture toughness of the glass are improved, the problem of fragility of existing glass is solved, and the performance of high strength, high mold and fracture resistance is achieved. It is suitable for Modern electronic products and aerospace applications.

CN115583795BActive Publication Date: 2024-12-31CAIHONG GRP SHAOYANG SPECIAL GLASS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211319353.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2024-12-31
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The fracture toughness and elastic modulus of existing glass are low, resulting in fragility of glass and cannot meet the drop resistance requirements of modern electronic products, especially large-size screens.

Method used

By preparing a high-strength, high-mode, fracture-resistant aluminosilicate glass, specific raw material component ratios and process flows, including SiO2, Al2O3, B2O3, Na2O, K2O, MgO, P2O5, SnO and high-coordinated metal oxidation The additives are melted, homogenized, molded and annealed to improve the elastic modulus and fracture toughness of the glass.

Benefits of technology

The glass has significantly improved its fracture resistance, with an elastic modulus of 67GPa to 82GPa and a fracture toughness of 0.825MPa·m1/2 to 1.024MPa·m1/2, which is suitable for protection of mobile display devices and aerospace fixed devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115583795B_ABST
    Figure CN115583795B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength, high-modulus, fracture-resistant aluminosilicate glass, a preparation method and an application thereof, wherein the molar percentage of the raw material components is 55%-70% of SiO 2 , 7%-15% Al 2 O 3 , 0%-5% B 2 O 3 , 6%-15% Na 2 O, 0-10% K 2 O, 0-10% MgO, 0.5-2% P 2 O 5 , 0.1% to 1% SnO and 0.3-1.5% of a modifying additive are mixed evenly, and then melted, homogenized, formed, clarified and annealed to obtain a high-strength, high-modulus, fracture-resistant glass. The aluminosilicate glass prepared according to the above components has high strength, high elastic modulus and fracture toughness, and has better anti-fragmentation ability, thereby broadening the application range of aluminosilicate glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminosilicate glass preparation, in particular to a high-strength, high-modulus, fracture-resistant aluminosilicate glass and a preparation method and application thereof.

[0002] As we all know, the intrinsic strength of glass is very high. Although there are differences in the records in different documents, it is basically between 10 and 14 GPa. However, the actual strength of glass is only 140 MPa, which is several orders of magnitude lower than the theoretical strength. In terms of actual strength, the tensile strength is only 1 / 8 to 1 / 10 of the compressive strength, especially the impact strength is lower, which makes the glass easy to break, causing casualties and property losses.

[0003] With the development of social economy and science and technology, while promoting the increasingly complete segmentation of electronic products, the competition in the electronic products industry has become increasingly fierce. At a time when performance improvement is basically saturated, the "fall resistance" of the screen has become a factor that manufacturers tend to ignore, but consumers pay great attention to. At present, the "lightness and thinness" and "large size" of the screen have become selling points pursued by many manufacturers. However, the larger the screen and the thinner the body, the higher the performance requirements for the cover glass. Therefore, an aluminosilicate glass with excellent mechanical properties, especially outstanding performance in hardness, elastic modulus and toughness, and suitable for chemical strengthening has great market value. The present invention aims to effectively solve the problem of glass shattering by improving the elastic modulus and fracture toughness of the glass. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a high-strength, high-modulus, fracture-resistant aluminosilicate glass and a preparation method and application thereof, which effectively improves the elastic modulus and fracture toughness of the glass and effectively solves the problem of glass breakage.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing high-strength, high-modulus, fracture-resistant aluminosilicate glass, characterized in that, in terms of molar percentage, the component raw materials include: 55%-70% SiO2, 7%-15% Al2O3, 0%-5% B2O3, 6%-15% Na2O, 0-10% K2O, 0-10% MgO, 0.5-2% P2O5, 0.1%-1% SnO and 0.3%-1.5% high-coordination metal oxide additives;

[0007] The specific preparation process is as follows:

[0008] SiO2, Al2O3, B2O3, Na2O, K2O, MgO, P2O5, SnO2 and high-coordination metal oxide additives are mixed evenly, and then melted, homogenized, formed, clarified and annealed to obtain high-strength, high-modulus and fracture-resistant glass.

[0009] Preferably, the molar percentages of Al2O3 and B2O3, R2O and RO satisfy the following relationship:

[0010] 1<(R2O+RO) / (Al2O3+B2O3)<3;

[0011] Wherein, R is a metal element; R2O+RO represents the total molar addition amount of alkali metal and alkaline earth metal oxides in the raw material components.

[0012] Preferably, the molar percentage of Na2O is 6%-14%, the molar percentage of K2O is 0-5%, and the molar percentage of MgO is 4%-8%.

[0013] Preferably, the high-coordination metal oxide additive is one of La2O3, Y2O3, ZrO2, TiO2 or CeO2; the molar percentage of the high-coordination metal oxide additive is 0.5%-1%.

[0014] Preferably, the melting, homogenizing and clarifying treatment includes four stages: the first stage is heated to 1000-1350°C, the heating rate during the heating process is 7°C / min, and the temperature is kept constant for 1 hour; the heating temperature in the second stage is 1350-1450°C, and the holding time after the temperature is constant is 1.5-2.5 hours; the heating temperature in the third stage is 1450-1550°C, and the holding time after the temperature is constant is 2-3 hours; the heating temperature in the fourth stage is 1550-1680°C, and the holding time after the temperature is constant is 3-6 hours.

[0015] Preferably, the annealing includes three stages: the heating temperature of the first stage is 600-650°C and the holding time is 1.5-3h, the heating temperature of the second stage is 300-450°C and the annealing rate is 6°C / h; the heating temperature of the third stage is 100-450°C and the annealing rate is 15°C / h.

[0016] Preferably, the fracture toughness of the high-strength, high-modulus, fracture-resistant aluminosilicate glass is 0.825 MPa·m 1 / 2 To 1.024MPa·m 1 / 2 .

[0017] Preferably, the elastic modulus of the high-strength, high-modulus, fracture-resistant aluminosilicate glass is 67 GPa to 82 GPa.

[0018] A high-strength, high-modulus and fracture-resistant aluminosilicate glass is prepared by the preparation method.

[0019] A high-strength, high-modulus, fracture-resistant aluminosilicate glass is used in the protection of mobile display devices / vehicle-mounted and aerospace fixed devices.

[0020] Compared with the prior art, the present invention has the following beneficial technical effects:

[0021] The high-strength, high-modulus, fracture-resistant aluminosilicate glass prepared by the present invention overcomes the problems of low fracture toughness and low elastic modulus of conventional glass, and effectively improves the fracture resistance of glass. The fracture toughness of the aluminosilicate glass is 0.825 MPa·m 1 / 2 To 1.024MPa·m 1 / 2 , and the elastic modulus is 67 GPa to 82 GPa. The high-strength, high-modulus, fracture-resistant aluminosilicate glass of the present invention is used in the protection of mobile display devices / vehicle-mounted and aerospace fixed devices.

[0022] The invention discloses a high-strength, high-modulus, fracture-resistant aluminosilicate glass, which comprises, by molar percentage, 55%-70% SiO2, 7%-15% Al2O3, 0%-5% B2O3, 6%-15% Na2O, 0-10% K2O, 0-10% MgO, 0.5-2% P2O5, 0.1%-1% SnO2 and a high-coordination metal oxide additive. The preparation process of the invention is simple, and the aluminosilicate glass has both the hardness of a rigid material and the toughness of a soft material under the influence of the metal oxide component, thereby constituting a higher intrinsic strength of the aluminosilicate glass. At the same time, after chemical strengthening, the crack propagation on the surface of the glass can be further hindered, thereby improving the strength of the glass. Conventional aluminosilicate glass has low fracture resistance and low elastic modulus, and the glass surface is easily broken by impact.

[0023] Furthermore, SiO2 is the most important network former in silicate glass and plays the role of the main skeleton in the glass system. Increasing the SiO2 content will strengthen the glass skeleton structure, but the viscosity of the glass liquid at the same temperature will increase, and the melting and clarification temperatures will increase to varying degrees. Therefore, an appropriate SiO2 content is a basic condition for glass formation.

[0024] Furthermore, Al2O3 cannot form glass alone, but it can have an important impact on the network structure of glass. It mainly exists in the form of aluminum-oxygen tetrahedral coordination structure and has a negative charge itself. It will be affected by external neutralizing ions. An appropriate amount of Al2O3 can improve the chemical stability of glass, improve the solubility and devitrification of glass. When its content is high, it will reduce the toughness of the glass and make the glass more brittle.

[0025] Furthermore, MgO has two coordination states in the glass, which is in an intermediate state. However, when the alkali metal content is insufficient, magnesium ions will not enter the network and only serve as network external bodies. 2+ The outer electron structure of Mg belongs to the inert gas configuration, and its polarization ability depends on the size of the ion radius. 2+ The ion radius is smaller and the ability to bind charges is slightly greater, so its field strength and polarization ability are greater, and its ability to separate the glass into phases is also stronger; MgO can increase the elastic modulus of glass to a certain extent, further improve the toughness of glass, and improve the stability and mechanical strength of glass.

[0026] Furthermore, Y2O3 and La2O3 are often used as effective dopants to improve the mechanical properties and chemical stability of glass due to their high melting points and high densities. Relevant literature shows that in systems such as germanic acid, boric acid, and phosphate, the mechanical properties of glass increase with the increase of yttrium oxide or lanthanum oxide, while the melting temperature decreases. Both have a significant effect on increasing the toughness, Young's modulus, and hardness of glass, but it is not advisable to add too much to the glass composition, otherwise the glass will become prone to devitrification and reduce the manufacturability of the glass.

[0027] Furthermore, CeO2 has the characteristics of high electric charge and high field strength. It not only reduces the viscosity of glass, improves the clarification effect of glass liquid and eliminates bubbles, but also adds CeO2 to the glass components to promote the connection of the glass network skeleton, increase the bridging oxygen in the glass network structure, and make the connection between silicon-oxygen tetramers closer. The resulting glass has a compact structure, and the mechanical properties and alkali resistance of the material are improved.

[0028] Furthermore, TiO2 belongs to the transition oxide group, and doping TiO2 helps Al 3+ Entering the glass network structure, Al 3+ The network filling and accumulation effect of TiO2 strengthens the glass network structure; when a small amount of TiO2 is doped, 4+ Partially replaced Si 4+ Into the glass network structure, but with the increase of TiO2 content, Ti 4+ It separates from the glass network and changes from the network structure position to the network gap position, gradually reducing the degree of aggregation of the glass network structure, but excessive amount will increase the tendency of crystallization and devitrification of the glass.

[0029] Furthermore, ZrO2 can be used as a glass network former, which can significantly increase the strength, thermal stability and corrosion resistance of glass; Zr belongs to the second transition series element, and its electronic configuration is 4d 2 5s 2It has a four-electron structure, and has tetragonal and hexagonal structures in its coordination structure. It can produce a hexacoordinate structure and enter the glass network structure. It usually exists in zirconium-silicon glass in the form of [ZrO6] coordination structure. The zirconium atoms are separated by at least two silicon-oxygen tetrahedra. The bond strength of Zr-O-Si is relatively high and difficult to break at high temperatures. However, excessive ZrO2 will increase the number of coordination structures. 4+ The ionic radius is large, and this group belongs to a network modifier in the glass structure, which will cause a tendency to crystallize. In addition, adding zirconium ions to the glass components can promote a more uniform distribution of other ions in the glass structure, but it will increase the high-temperature viscosity of the glass.

[0030] Furthermore, the aluminosilicate glass of the present invention is mixed according to the ratio given above, wherein the high-coordination metal oxide additive can be added alone or as a mixture of the two. The appropriate ratio is the key to achieving optimal performance. Therefore, the present invention exhibits high-strength, high-modulus, and fracture-resistant aluminosilicate glass through specific formula ratios and performance results. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart for preparing the high-strength, high-modulus, fracture-resistant aluminosilicate glass. DETAILED DESCRIPTION

[0032] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0033] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0034] A high-strength, high-modulus, fracture-resistant aluminosilicate glass comprises, by mole percentage, 55%-70% SiO2, 7%-15% Al2O3, 0%-5% B2O3, 6%-15% Na2O, 0-10% K2O, 0-10% MgO, 0.5-2% P2O5, 0.1%-1% SnO and a high-coordination metal oxide additive.

[0035] Preferably, the molar percentage of Na2O is 6%-14%, the molar percentage of K2O is 0-5%, and the molar percentage of MgO is 4-8%.

[0036] Preferably, the molar percentages of Al2O3 and B2O3 to R2O and RO satisfy the following relationship: 1<(R2O+RO) / (Al2O3+B2O3)<3. Wherein, R is a metal element; and R2O+RO represents the total molar addition amount of alkali metal and alkaline earth metal oxides in the raw material components.

[0037] Preferably, the high-coordination metal oxide additive in the formula may be a rare earth metal oxide of La or Y.

[0038] Preferably, the high coordination metal oxide additive in the formulation may be a metal oxide of Zr, Ti or Ce.

[0039] Preferably, the high-coordination metal oxide additive may be a rare earth metal oxide of La or Y, with a molar percentage of 0.3%-1.5%.

[0040] Preferably, the high-coordination metal oxide additive may be a metal oxide of Zr, Ti or Ce, with a molar percentage of 0.5%-1%.

[0041] Preferably, the method for preparing aluminosilicate glass from the glass composition is as follows: Figure 1 As shown, the method comprises the following steps:

[0042] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0043] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in sequence. In the first stage, heat to 1000-1350°C. During the heating process, the crucible temperature rises at a rate of 7°C / min. After the temperature is constant, keep warm for 1 hour. In the second stage, the temperature is heated to 1350-1450°C for 1.5-2.5 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1450-1550°C for 2-3 hours. In the fourth stage, the temperature is heated to 1550-1680°C for 3-6 hours.

[0044] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0045] Step 4: After demolding, annealing is performed. The annealing includes three stages: the temperature of the first stage is 600-650°C, the holding time is 1.5-3h, the temperature of the second stage is 300-450°C, the annealing rate is 6°C / h, and the temperature of the third stage is 100-450°C, the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0046] The high-strength, high-modulus, fracture-resistant aluminosilicate glass of the present invention is used in the protection of mobile display devices / vehicle-mounted and aerospace fixed devices.

[0047] Embodiment 1,

[0048] A high-strength, high-modulus, fracture-resistant aluminosilicate glass, comprising, by mole percentage: 67.95% SiO2, 11.01% Al2O3, 0.5% B2O3, 10.75% Na2O, 2.43% K2O, 6.75% MgO, 0.5% P2O5, 0.11% SnO2

[0049] The molar percentages of Al2O3 and B2O3, R2O and RO satisfy the following relationship:

[0050] R2O+RO is 19.93%, (R2O+RO) / (Al2O3) is 1.51,

[0051] The method for preparing aluminosilicate glass from the glass composition comprises the following steps:

[0052] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0053] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in turn. In the first stage, heat to 1000°C. During the heating process, the crucible heats up at a rate of 7°C / min and is kept at a constant temperature for 1 hour. In the second stage, the temperature is heated to 1350°C for 1.5 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1450°C for 2 hours. In the fourth stage, the temperature is heated to 1550°C for 36 hours.

[0054] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0055] Step 4: After demolding, annealing is carried out. The annealing includes three stages: the temperature of the first stage is 600°C and the holding time is 1.5h, the temperature of the second stage is 300°C and the annealing rate is 6°C / h, and the temperature of the third stage is 100°C and the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0056] According to the proportion of oxides in Tables 1 to 2, raw materials are weighed and mixed to form aluminosilicate glass batch material samples. Examples 1 to 14 are high-strength, high-modulus, and fracture-resistant aluminosilicate glasses prepared by adding different amounts of raw materials of different components. The preparation environment of each example is the same, and the melting is carried out in a muffle furnace according to the same preparation method as the above Example 1 until a high-strength, high-modulus, and fracture-resistant aluminosilicate glass with uniform stress is formed after annealing.

[0057] Embodiment 15

[0058] A high-strength, high-modulus, fracture-resistant aluminosilicate glass, comprising, by mole percentage, 55.0% SiO2, 7% Al2O3, 5% B2O3, 13% Na2O, 10% K2O, 10% MgO, 0.5% P2O5, 1% SnO2 and 1.5% La2O3;

[0059] The method for preparing aluminosilicate glass from the glass composition comprises the following steps:

[0060] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0061] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in turn. In the first stage, heat to 1000°C. During the heating process, the crucible heats up at a rate of 7°C / min and is kept at a constant temperature for 1 hour. In the second stage, the temperature is heated to 1350°C for 1.5 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1450°C for 2 hours. In the fourth stage, the temperature is heated to 1550°C for 36 hours.

[0062] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0063] Step 4: After demolding, annealing is carried out. The annealing includes three stages: the temperature of the first stage is 600°C and the holding time is 1.5h, the temperature of the second stage is 300°C and the annealing rate is 6°C / h, and the temperature of the third stage is 100°C and the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0064] Embodiment 16,

[0065] A high-strength, high-modulus, fracture-resistant aluminosilicate glass, comprising, by mole percentage, 70% SiO2, 15% Al2O3, 0% B2O3, 12% Na2O, 0% K2O, 0% MgO, 2% P2O5, 0.1% SnO2 and 0.9% La2O3

[0066] The method for preparing aluminosilicate glass from the glass composition comprises the following steps:

[0067] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0068] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in turn. In the first stage, heat to 1280°C. During the heating process, the crucible temperature rises at a rate of 7°C / min and is kept constant for 1 hour. In the second stage, the temperature is heated to 1400°C for 2 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1520°C for 2.1 hours. In the fourth stage, the temperature is heated to 1580°C for 3.5 hours.

[0069] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0070] Step 4: After demolding, annealing is carried out. The annealing includes three stages: the temperature of the first stage is 630°C and the holding time is 2h, the temperature of the second stage is 340°C and the annealing rate is 6°C / h, and the temperature of the third stage is 240°C and the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0071] Embodiment 17,

[0072] A high-strength, high-modulus, fracture-resistant aluminosilicate glass, comprising, by mole percentage, 58.5% SiO2, 12% Al2O3, 2.5% B2O3, 15% Na2O, 5% K2O, 5% MgO, 1.2% P2O5, 0.5% SnO2 and 0.3% La2O3

[0073] The method for preparing aluminosilicate glass from the glass composition comprises the following steps:

[0074] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0075] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in turn. In the first stage, heat to 1350°C. During the heating process, the crucible temperature rises at a rate of 7°C / min and is kept constant for 1 hour. In the second stage, the temperature is heated to 1450°C for 2.5 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1550°C for 3 hours. In the fourth stage, the temperature is heated to 1680°C for 6 hours.

[0076] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0077] Step 4: After demolding, annealing is carried out. The annealing includes three stages: the temperature of the first stage is 650°C and the holding time is 3h, the temperature of the second stage is 450°C and the annealing rate is 6°C / h, and the temperature of the third stage is 450°C and the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0078] Embodiment 18,

[0079] A high-strength, high-modulus, fracture-resistant aluminosilicate glass, comprising, by mole percentage, 66.5% SiO2, 10% Al2O3, 1.5% B2O3, 8.5% Na2O, 5.5% K2O, 6.5% MgO, 1.8% P2O5, 0.2% SnO2 and 0.5% La2O3

[0080] The method for preparing aluminosilicate glass from the glass composition comprises the following steps:

[0081] Step 1: convert the molar ratio of SiO2, Al2O3, B2O3, Na2O, K2O, MgO, SnO2 and high-coordination metal oxide additive into a weight ratio, take the corresponding weight of the above ingredients and mix them evenly at room temperature;

[0082] Step 2: Divide the mixed raw materials into three equal parts and add them into a platinum crucible in turn. In the first stage, heat to 1280°C. During the heating process, the crucible temperature rises at a rate of 7°C / min and is kept constant for 1 hour. In the second stage, the temperature is heated to 1400°C for 2 hours. The raw materials are fully melted in the first two stages. In the third stage, the temperature is heated to 1520°C for 2.1 hours. In the fourth stage, the temperature is heated to 1580°C for 3.5 hours.

[0083] Step 3: After clarification, pour the glass liquid into a mold made of ductile cast iron;

[0084] Step 4: After demolding, annealing is carried out. The annealing includes three stages: the temperature of the first stage is 630°C and the holding time is 2h, the temperature of the second stage is 380°C and the annealing rate is 6°C / h, and the temperature of the third stage is 380°C and the annealing rate is 15°C / h; after 100°C, the power is turned off to room temperature, and finally a high-strength, high-modulus, fracture-resistant aluminosilicate glass is obtained.

[0085] Table 1 Basic properties of glass samples of Examples 1 to 8 of the present invention

[0086] Example 1 2 3 4 5 6 7 <![CDATA[SiO2(mol%)]]> 67.95 68.15 68.85 69.26 69.52 69.79 69.79 <![CDATA[Al2O3(mol%)]]> 11.01 10.88 10.78 11.35 11.38 11.74 11.74 <![CDATA[B2O3(mol%)]]> 0.5 0.5 0.5 1 1 1.05 1.05 <![CDATA[Na2O(mol%)]]> 10.75 10.35 10.25 9.86 9.58 10.52 10.52 <![CDATA[K2O(mol%)]]> 2.43 2.43 2.43 2.43 2.43 1.43 1.43 MgO(mol%) 6.75 6.26 6.06 5.64 5.73 5.59 5.59 <![CDATA[P2O5(mol%)]]> 0.5 1 0.5 0.5 0.5 1 1 <![CDATA[SnO2(mol%)]]> 0.11 0.11 0.11 0.11 0.11 0.11 0.11 <![CDATA[La2O3(mol%)]]> 0 0.32 0.52 0.85 0 0.45 0.32 <![CDATA[Y2O3(mol%)]]> 0 0 0 0 0.75 0.32 0.45 total 100 100 100 100 100 100 100 <![CDATA[R2O+RO]]> 19.93 19.04 18.74 17.93 17.74 17.54 17.54 <![CDATA[(R2O+RO) / (Al2O3+B2O3)]]> 1.732 1.673 1.661 1.452 1.433 1.371 1.371 <![CDATA[Density (g / cm 3 )]]> 2.245 2.337 2.358 2.384 2.368 2.415 2.395 Annealing point(℃) 633 630 621 614 648 654 612 Strain point(℃) 601 595 574 565 593 587 554 Softening point(℃) 919 908 889 862 878 864 875 Liquidus temperature(℃) 989 976 960 Devitrification 970 985 950 Molding temperature (35kP) 1201 1189 1185 1178 1180 1193 1190 Elastic modulus(GPa) 66.48 67 70 76 72 78 75 <![CDATA[Fracture toughness (Mpa·m 0.5 )]]> 0.698 0.825 0.831 0.813 0.855 0.872 0.86 <![CDATA[Vickers hardness (Kgf / mm 2 )]]> 512 575 601 621 609 673 648

[0087] The following examples are all prepared by the preparation method described above in the present invention, wherein the annealing process needs to adjust the annealing temperature setting according to different formulations.

[0088] According to the proportion of oxides in Tables 1 to 2, the raw materials are weighed and mixed to form aluminosilicate glass batch material samples, and melted in a muffle furnace according to the above preparation method until a glass sample with uniform stress is formed after annealing. According to the Archimedean drainage method, the density of the aluminosilicate glass sample is tested using an analytical balance (accuracy 0.0001g), and the number of test samples in each group is ≥3; the annealing point, strain point and softening point of the glass are determined by fiber elongation; the liquidus temperature of the sample is measured using a gradient furnace and a polarizing microscope; the elastic modulus of the sample is tested using a MK-6A elastic modulus tester; the Vickers hardness test is to press the Vickers indenter into the glass surface with a test force, keep it for a specified time, remove the test force, measure the diagonal length of the indentation on the glass surface, and obtain the Vickers hardness value of the measured sample through the formula Vickers hardness HV = constant * test force / indentation area; the fracture toughness is pre-cracked by the indentation method, and then calculated by the diagonal crack length, load and elastic modulus.

[0089] Table 2 Basic properties of glass samples of Examples 8 to 14 of the present invention

[0090] Example 8 9 10 11 12 13 14 <![CDATA[SiO2(mol%)]]> 67.65 68.15 68.85 67.26 67.51 66.39 66.39 <![CDATA[Al2O3(mol%)]]> 11.75 10.45 10.74 11.45 11.38 12.14 12.14 <![CDATA[B2O3(mol%)]]> 0.5 0.5 0.5 1 1 1.05 1.05 <![CDATA[Na2O(mol%)]]> 10.75 10.35 10.25 10.86 10.78 11.54 11.38 <![CDATA[K2O(mol%)]]> 1.43 2.43 2.43 2.43 2.43 1.43 1.43 MgO(mol%) 67.65 68.15 68.85 67.26 67.51 66.39 66.39 <![CDATA[P2O5(mol%)]]> 0.5 1 0.5 0.5 0.5 1 1 <![CDATA[SnO2(mol%)]]> 0.11 0.11 0.11 0.11 0.11 0.11 0.11 <![CDATA[CeO2(mol%)]]> 0.56 0.75 0 0 0 0 0.23 <![CDATA[TiO2(mol%)]]> 0 0 0.56 0.75 0 0 0.16 <![CDATA[ZrO2(mol%)]]> 0 0 0 0 0.56 0.75 0.52 total 100 100 100 100 100.01 100 100 <![CDATA[R2O+RO]]> 18.93 19.04 18.74 18.93 18.94 18.56 18.4 <![CDATA[(R2O+RO) / (Al2O3+B2O3)]]> 1.545 1.739 1.667 1.52 1.53 1.407 1.395 <![CDATA[Density (g / cm 3 )]]> 2.427 2.475 2.325 2.347 2.359 2.371 2.41 Annealing point(℃) 617 612 630 625 624 634 610 Strain point(℃) 578 569 574 565 605 610 554 Softening point(℃) 885 860 900 892 897 874 856 Liquidus temperature(℃) 1023 963 906 953 970 826 843 Molding temperature (35kP) 1201 1189 1185 1178 1180 1193 1190 Elastic modulus(GPa) 78 74 69 72 72 75 82 <![CDATA[Fracture toughness (Mpa·m 0.5 )]]> 0.971 0.842 0.853 0.858 0.864 0.872 1.024 <![CDATA[Vickers hardness (Kgf / mm 2 )]]> 675 655 601 621 609 654 704

[0091] From the above data, we can see that after adding high-coordinated metal oxide additives, the elastic modulus, fracture toughness and hardness are all improved to varying degrees. If the content of high-coordinated metal oxide additives is too high, glass devitrification will occur. At the same time, the interaction with alkali metals will make the hardness too large and the toughness reduced. The influence of tetravalent oxides Ce, Ti, and Zr on strength is slightly stronger than that of trivalent metal oxides La and Y. In addition, when two or more metal oxides are mixed with each other, the strength can reach the optimal value, which means that the number of bridging oxygen bonds inside the glass reaches the maximum, thereby making the mechanical properties of the glass reach the best.

[0092] The radius of yttrium ion itself (0.09nm) is much larger than that of silicon ion (0.04pm). If the Y2O3 content is too high, the large-sized ions will inevitably cause the internal structure of the glass to be distorted to a certain extent. Driven by thermal energy, the distorted network structure is more likely to vibrate, which will further reduce the chemical stability of the glass. Therefore, the molar percentage of Y2O3 is preferably 0.75.

[0093] The above results further illustrate that doping with an appropriate amount of CeO2 can increase the number of bridging oxygens in the glass, make the structure denser, and significantly improve the mechanical properties. However, excessive doping will increase the number of non-bridging oxygens in the glass structure, resulting in a decrease in the mechanical properties of the glass.

[0094] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any ordinary technician in the industry can smoothly implement the present invention as shown in the drawings and described above. However, any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A high-strength, high-modulus, fracture-resistant aluminosilicate glass, characterized in that: In terms of molar percentage, the raw materials include: 58.5%-68.85% SiO2, 10.78%-12% Al2O3, 0%-2.5% B2O3, 10.25%-15% Na2O, 0-5% K2O, 0-6.75% MgO, 0.5-2% P2O5, 0.1%-0.5% SnO2 and 0.3%-0.9% high coordination metal oxide additive; the high coordination metal oxide additive is La2O3; The fracture toughness of the high-strength, high-modulus, fracture-resistant aluminosilicate glass is 0.825 MPa·m 1 / 2 To 0.831MPa·m 1 / 2 ; The elastic modulus of the high-strength, high-modulus, fracture-resistant aluminosilicate glass is 67 GPa to 70 GPa; The molar percentages of Al2O3 and B2O3, R2O and RO satisfy the following relationship: 1<(R2O+RO) / (Al2O3+B2O3)<3; Wherein, R is a metal element; R2O+RO represents the sum of the molar addition amounts of alkali metal and alkaline earth metal oxides in the raw material components; The specific preparation process of the high-strength, high-modulus, fracture-resistant aluminosilicate glass is as follows: SiO2, Al2O3, B2O3, Na2O, K2O, MgO, P2O5, SnO2 and high-coordination metal oxide additives are mixed uniformly, and then melted, homogenized, formed, clarified and annealed to obtain high-strength, high-modulus and fracture-resistant glass; The melting, homogenizing and clarifying treatment includes four stages: in the first stage, the temperature is heated to 1000-1350°C, the heating rate during the heating process is 7°C / min, and the temperature is kept constant for 1 hour; in the second stage, the heating temperature is 1350-1450°C, and the holding time is 1.5-2.5 hours after the temperature is constant; in the third stage, the heating temperature is 1450-1550°C, and the holding time is 2-3 hours after the temperature is constant; in the fourth stage, the heating temperature is 1550-1680°C, and the holding time is 3-6 hours after the temperature is constant.

2. The method for preparing a high-strength, high-modulus, fracture-resistant aluminosilicate glass according to claim 1, characterized in that: The annealing includes three stages: the heating temperature of the first stage is 600-650°C and the holding time is 1.5-3h; the heating temperature of the second stage is 300-450°C and the annealing rate is 6°C / h; the heating temperature of the third stage is 100-450°C and the annealing rate is 15°C / h.

3. Application of the high-strength, high-modulus, fracture-resistant aluminosilicate glass as claimed in claim 1 in the protection of mobile display devices / vehicle-mounted and aerospace fixed devices.